Imprinted effects on the boric acid removal from water by molecularly imprinted polymer: Synthesis and characterization - Nurlin, Abu Samah; Nurjannah, Salim; Kamrul Fakir, Kamarudin (John Wiley & Sons, Inc., 2025)
In the present work, a study of boron removal from water using molecularly imprinted polymer-boric acid (MIP-BA) is conducted. This study is significant as it can be an addition for removing boric species, particularly in cases when carbon in tertiary treatment is ineffective. Kinetic study, saturation study and pH effect are among the parameters chosen to characterize the sorption characteristics of MIP-BA using Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES) detection. In the kinetic study in batch mode, boron is removed at an efficiency removal of 80.18% after 5 mins before stabilizing over 60 min. The adsorption process is deduced to be chemisorption in adsorption kinetic modelling studies. In the saturation study, the adsorption capacity of MIP-BA is increased. The adsorption isotherm study conveyed that there is a monolayer adsorption on homogenous surface of MIP-BA as Langmuir’s model posted a R2 value of 0.9932 bettering 0.9832 posted by Freundlich’s model. The optimal pH for boron removal is pH 8.7 (87.93%). The hydroxyl group readily forms covalent bonds with boron when reacted with boric acid in alkali medium. Non imprinted polymer (NIP) is effective at extracting boron from water, reducing the cost of cleaning the polymer with a Soxhlet equipment.